Drought Sensitivity of the Carbon Isotope Composition of Leaf Dark-Respired CO2 in C3 (Leymus chinensis) and C4 (Chloris virgata and Hemarthria altissima) Grasses in Northeast China - Zhong, Shangzhi; Chai, Hua; Xu, Yueqiao; Li, Yan; Ma, Jian-Ying; Sun, Wei (Frontiers in Plant Science, 2017)
Whether there are photosynthetic pathway differences exist in the amplitude of nighttime variations in the carbon isotope composition of leaf dark-respired CO2 (δ13Cl) and respiratory apparent isotope fractionation relative to biomass (ΔR,biomass) in response to drought stress is unclear. These differences, if present, would be important for the partitioning of C3-C4 mixed ecosystem C fluxes. We measured δ13Cl, the δ13C of biomass and of potential respiratory substrates and leaf gas exchange in a one C3 (Leymus chinensis) and two C4 (Chloris virgata and Hemarthria altissima) grasses during a manipulated drought period. For all studied grasses, δ13Cl decreased from 2100 h to 0300 h. The magnitude of the nighttime shift in δ13Cl decreased with increasing drought stress. The δ13Cl values were correlated with the δ13C of respiratory substrates, whereas the magnitude of the nighttime shift in δ13Cl strongly depended on the daytime carbon assimilation rate and the range of nighttime variations in the respiratory substrate content. The ΔR,biomass in the C3 and C4 grasses varied in opposite directions with the intensification of the drought stress. The contribution of C4 plant-associated carbon flux is likely to be overestimated if carbon isotope signatures are used for the partitioning of ecosystem carbon exchange and the δ13C of biomass is used as a substitute for leaf dark-respired CO2. The detected drought sensitivities in δ13Cl and differences in respiratory apparent isotope fractionation between C3 and C4 grasses have marked implications for isotope partitioning studies at the ecosystem level.